Day 2 Tue, November 08, 2016 2016
DOI: 10.2118/183343-ms
|View full text |Cite
|
Sign up to set email alerts
|

Debottlenecking of FPSO Facilities by Compact Separators

Abstract: The Bonga FPSO was designed to process 280 MBLPD gross liquid, constrained by the three-phase low pressure (LP) separator capacity. The projected production forecast indicated that additional future volumes of produced fluids from the Bonga field could exceed the design capacity of the installation. FMC's Inline PhaseSplitter was identified as a solution for debottlenecking the three-phase LP separator liquid handling capacity. The PhaseSplitter is a compact pipe-based cyclonic separator that splits the feed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…The liquid holdup that existed during the critical ZNLF is called critical ZNLF holdup. By grouping some of the critical ZNLF holdup, a trend was realised that agreed with existing data by Kouba et al, and Apardi et al, that is: the critical ZNLF holdup decrease with increasing separator inlet superficial gas velocity [4,6]. Additionally, it was found that the critical ZNLF holdup increases with increasing separator inlet superficial liquid velocity.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The liquid holdup that existed during the critical ZNLF is called critical ZNLF holdup. By grouping some of the critical ZNLF holdup, a trend was realised that agreed with existing data by Kouba et al, and Apardi et al, that is: the critical ZNLF holdup decrease with increasing separator inlet superficial gas velocity [4,6]. Additionally, it was found that the critical ZNLF holdup increases with increasing separator inlet superficial liquid velocity.…”
Section: Resultssupporting
confidence: 81%
“…Liquid holdup under ZNLF for a stagnant liquid condition was measured using electrical resistance tomography. The trend of present data of ZNLF holdup under stagnant liquid condition agrees with that reported by Kouba et al, [4] and Apardi et al, [6]. However, quantitatively, their data are not comparable with the present data, as the effect of inlet liquid flow on ZNLF was not considered in their work.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation